Transcriptome analysis of early embryonic development in a mouse model of polycystic ovary syndrome - Han, Shan; Lv, Jiale; Sun, Xuedong; Xie, Yanqiu; Shi, Yuhua (Frontiers in Cell and Developmental Biology, 2025)
Polycystic ovary syndrome (PCOS) is a complex disorder that originates during fetal development and significantly impairs female fertility during the reproductive years. Although it is hypothesized that prenatal exposure to elevated androgen levels plays a crucial role in the pathogenesis of PCOS, the precise effects of such exposure on the offspring of individuals with PCOS remain unclear. In this study, we established a mouse model of PCOS by administering dihydrotestosterone (DHT) prenatally. We subsequently evaluated the reproductive phenotype and fertility of the PCOS-like mice, focusing on ovarian function and embryo developmental potential. Smart-seqII RNA sequencing was performed on blastocysts to obtain the RNA expression profile of preimplantation embryos from PCOS mice. These findings indicate that the PCOS model mice exhibit hyperandrogenic symptoms, reduced ovulation rates, and impaired development of oocytes and blastocysts compared to controls. Furthermore, 918 differentially expressed genes were identified in the blastocyst samples, with significant enrichment in pathways related to intracellular energy metabolism, tissue development, glycolipid metabolism, hormone synthesis, and inflammation. This research presents direct evidence that prenatal exposure to hyperandrogenism negatively influences the early embryonic development of offspring and plays a significant role in the later manifestation of polycystic ovary syndrome in adulthood. These findings contribute valuable insights for the early prevention of PCOS.